Allogenic platelet-rich plasma in induced ulcers in rat’s cornea - Gandolfi, M.g. [UNESP]; Brandão, C.v.s. [UNESP]; Pellizon, C.h. [UNESP]; Hirota, I.n. [UNESP]; Barros, R. [UNESP]; Hussein, A.c.b. [UNESP]; Merlini, N.b. [UNESP]; Takahira, R.k. [UNESP]; Mesquita, L.r. [UNESP] (Universidade Federal de Minas Gerais, Escola de Veterinária, 2021)
The objective in this study was to evaluate the clinic effect of applying allogenic platelet-rich plasma (PRP) heated or not, for treating cornea ulcers, including the dosage of PDGF-BB in the cornea. The ulcers were induced, standardizing the left eye from 81 rats (Ratus norvegicus, albinus variety), assigned randomly into three groups (N=27): control group (CG) which did not receive any topic treatment; heated PRP group (GA) and PRP group (GP), which received topical treatment every eight hours for five days. Each group underwent evaluation at 24 hours (M1), three days (M3) and five days (M5). The clinical exam evaluated the opacity, vascularization and corneal repair. The corneal PDGF-BB was dosed through the ELISA method. The corneal opacity was decreased in PRP-treated animals (GA and GP) and corneal repair time reduced when compared to CG at M1 and M5. Furthermore, GP showed greater vascularization at M3 compared to M1. Applied allogenic PRP eye drops, heated or not, speed up corneal healing, and reduce corneal repair time. However, the corneal PDGF concentration was not altered in any of the treatments.

Objetivou-se avaliar o efeito clínico da aplicação de plasma rico em plaquetas alogênico (PRP) aquecido ou não, no tratamento de úlceras de córnea, como a dosagem de PDGF-BB na córnea. As úlceras foram induzidas, padronizando-se o olho esquerdo de 81 ratos (Rattus norvegicus, variedade albinus), aleatoriamente, nos três grupos (N = 27): grupo controle (CG), que não recebeu nenhum tratamento tópico; grupo PRP aquecido (GA) e grupo PRP (GP), que receberam tratamento tópico a cada oito horas, durante cinco dias. Cada grupo foi subdividido em 24 horas (M1), três dias (M3) e cinco dias (M5). O exame clínico avaliou a opacidade, a vascularização e o reparo corneano. O PDGF-BB corneano foi dosado pelo método Elisa. Houve diminuição da opacidade da córnea nos animais tratados com PRP (GA e GP) e diminuição do tempo de reparo da córnea em comparação com CG, M1 e M5. Além disso, foi observada maior vascularização no GP no momento M3 em relação ao M1. A aplicação de colírios de PRP alogênico, aquecidos ou não, acelera a cicatrização da córnea, além de reduzir o tempo de reparo da córnea. No entanto, a concentração de PDGF na córnea não se alterou em nenhum dos tratamentos.
[Plasma rico em plaquetas alogênico em úlceras de córnea induzidas em ratos]
Keywords: heated platelet-rich plasma; growth factor; PDGF; plasma rich in growth factors; eye drops; plasma rico em plaquetas aquecido; fator de crescimento; PDGF; plasma rico em fatores de crescimento; colírios